HUBUNGAN ANTARA KESEPIAN DENGAN KONSEP DIRI MAHASISWA PERANTAU ASAL BANGKA YANG TINGGAL DI BANDUNG - Nara Syifa Saputri; Agus Abdul Rahman; Elisa Kurniadewi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research aims to empirically study about correlation between loneliness and self-concept of students from Bangka who stay in Bandung. Sample are 60 students taken through purposive sampling from 280 population. Result shows that there is significant correlation between loneliness and self concept with cooficient correlation -0,379 and significancy level (0,019). It is concluded that student having high loneliness will have low self-concept whereas those who have low loneliness their self-concept become positive.